The postgenomic condition : ethics, justice, and knowledge after the genome - Reardon, Jenny, 1972- (The University of Chicago Press, 2017)
While the sequencing of the human genome was a landmark achievement, the availability and manipulation of such a vast amount of data about our species has inevitably led to questions that are increasingly fundamental and urgent: now that information about human bodies can be transformed into a natural resource, how will and should we interpret and use it? With The Postgenomic Condition, Jenny Reardon draws on more than a decade of research in molecular biology labs, commercial startups, governmental agencies and civic spaces to examine the extensive efforts after the completion of the Human Genome Project to transform genomics from high tech informatics practiced by a few well-financed scientists and engineers to meaningful knowledge beneficial to all people. Through her in-depth profiles of genomic initiatives around the world, we see hopes to forge public knowledge and goods from blood and DNA meet the reality of limited resources and conflicting values. building the argument around the limits of liberal concepts of openness, information, inclusion, privacy, property and the public concepts that proved salient at different points in the unfolding story of efforts to make sense of human genomes Reardon shows how genomics challenges us to move beyond existing liberal frameworks to ask deeper questions of knowledge and justice.